Manipulation of the crosstalk between tumor angiogenesis and immunosuppression in the tumor microenvironment: Insight into the combination therapy of anti-angiogenesis and immune checkpoint blockade - Zheng, Weiwei; Qian, Cheng; Tang, Yu; Yang, Chunmei; Zhou, Yueke; Shen, Peiliang; Chen, Wenxing; Yu, Suyun; Wei, Zhonghong; Wang, Aiyun; Lu, Yin; Zhao, Yang (Frontiers in Immunology, 2022)
Immunotherapy has been recognized as an effective and important therapeutic modality for multiple types of cancer. Nevertheless, it has been increasing recognized that clinical benefits of immunotherapy are less than expected as evidenced by the fact that only a small population of cancer patients respond favorably to immunotherapy. The structurally and functionally abnormal tumor vasculature is a hallmark of most solid tumors and contributes to an immunosuppressive microenvironment, which poses a major challenge to immunotherapy. In turn, multiple immune cell subsets have profound consequences on promoting neovascularization. Vascular normalization, a promising anti-angiogenic strategy, can enhance vascular perfusion and promote the infiltration of immune effector cells into tumors via correcting aberrant tumor blood vessels, resulting in the potentiation of immunotherapy. More interestingly, immunotherapies are prone to boost the efficacy of various anti-angiogenic therapies and/or promote the morphological and functional alterations in tumor vasculature. Therefore, immune reprograming and vascular normalization appear to be reciprocally regulated. In this review, we mainly summarize how tumor vasculature propels an immunosuppressive phenotype and how innate and adaptive immune cells modulate angiogenesis during tumor progression. We further highlight recent advances of anti-angiogenic immunotherapies in preclinical and clinical settings to solidify the concept that targeting both tumor blood vessels and immune suppressive cells provides an efficacious approach for the treatment of cancer.